Combined treatment of electrical and ethylene-vinyl acetate copolymer (EVA) to improve the cold flowability of waxy crude oils. (1st May 2020) - Xie, Yiwei; Zhang, Jinjun; Ma, Chenbo; Chen, Chaohui; Huang, Qian; Li, Zixin; Ding, Yifei; Li, Hongying; Han, Shanpeng
Highlights: Combination of electric field and EVA can improve waxy oils' cold flowability. The combined treatment outperforms the individual treatments under low shearing. The combined treatment leads to larger size and broader size distribution of wax. Abstract: Flow assurance issues related to wax precipitation, are one of the most challenging problems in the pipeline transportation of waxy crude oils. Flowability of waxy oils can be improved by suitable pour point depressants (PPDs). Besides chemical treatments, exposing waxy oils to high-voltage electric fields can also significantly improve their cold flowability. However, the combined effect of electric fields and PPD on the flowability of waxy oils is not yet clear. In this investigation, the effect of the combined electrical and EVA treatment on the flow properties of a waxy crude oil was studied. It is found that the combined treatment can lead to more significant reductions in the viscosity, the yield stress and the thixotropy of waxy oils compared to oils treated solely by electric field or EVA. However, the overall improvement in the flowability achieved by the joint treatment is lower than the sum of improvements achieved by the electric field and EVA. The combined treatment outperforms the individual treatments for hours under a low shear of 10 s −1 . However, the performance cannot be preserved even for minutes under a high shear of 1200 s −1 . Reheating has a negative impact on the electrical treatment, but an intricate impact on the EVA treatment and the combined treatment. The electrical- and chemical performance both undermine upon reheating, but chemical performance can be partially recovered when reheating temperature is above the wax disappearance temperature. Microscopic observation showed that the combined treatment leads to larger size and broader size distribution of wax particles.